1990
DOI: 10.1161/01.atv.10.1.135
|View full text |Cite
|
Sign up to set email alerts
|

Influence of high density lipoprotein on esterified cholesterol stores in macrophages and hepatoma cells.

Abstract: The clearance of this intra-cellular cholesteryl ester is central to the process of regression of an atherosclerotic lesion. It is generally accepted that clearance of this ester is dependent on its hydrolysis to free cholesterol, with release of that cholesterol to an appropriate exogenous acceptor, and high density lipoprotein (HDL), or a specific subclass of HDL, is thought to mediate this clearance process. 3 Although there is an extensive literature on the efflux of free cholesterol from cells, 4 much les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 39 publications
4
29
0
1
Order By: Relevance
“…This may be due to several factors. J774 macrophages hydrolyze stored CE slower than primary mouse macrophages, 29,49 and J774 macrophages are a dividing cell population in which FC accumulation may be moderated by dilution due to cell growth. Both of these characteristics may serve to limit the FC accumulation and thereby prevent a nucleating event.…”
Section: Cholesterol Crystal Formationmentioning
confidence: 97%
“…This may be due to several factors. J774 macrophages hydrolyze stored CE slower than primary mouse macrophages, 29,49 and J774 macrophages are a dividing cell population in which FC accumulation may be moderated by dilution due to cell growth. Both of these characteristics may serve to limit the FC accumulation and thereby prevent a nucleating event.…”
Section: Cholesterol Crystal Formationmentioning
confidence: 97%
“…In some experiments, acLDL was incubated with UCphospholipid liposomes (225 g UC per mL) and BSA (10 mg/mL) overnight at 37°C before use in experiments. 17 During the course of these experiments, we found that the addition of liposomes and BSA to the medium containing acLDL did not further increase esterified cholesterol (EC) accumulation in HMMs, and these agents were subsequently omitted from the incubation medium. The concentration of acLDL used in these studies was based on our previous work in human THP-1 macrophages and on the work of other investigators studying foam cell formation in HMMs.…”
Section: Lipid Enrichment Of Cellsmentioning
confidence: 99%
“…After 3 days, the cells were washed and labeled with [ 3 H]cholesterol in the presence of 1 μg/mL Sandoz 58035, an inhibitor of intracellular cholesterol esterification, 28 during an overnight incubation in MEM containing 2.5% FBS. ACAT inhibitor compound 58035 was present at 1 μg/mL of media in cell labeling, cell equilibration, and cellular efflux stages.…”
Section: Cholesterol Flux Studiesmentioning
confidence: 99%
“…28 To generate cells that were both UC and EC enriched, Sandoz compound 58035 was omitted 28 during both cholesterol enrichment of the cells and the subsequent incubations with cholesterol acceptors.…”
Section: Cholesterol Flux Studiesmentioning
confidence: 99%